Why triage materials with low luminescence quantum efficiency: the use of 35Cbz4BzCN as a universal host for organic light emitting diodes through effective triplet energy transfer. Issue 7 (22nd January 2021) - Huang, Yi-Mei; Chen, Tse-Ying; Chen, Deng-Gao; Liang, Hsuan-Chi; Wu, Cheng-Ham; Lee, Mandy M.; Chiu, Tien-Lung; Lee, Jiun-Haw; Chiu, Yu-Cheng; Chou, Pi-Tai; Leung, Man-kit
Abstract : 35Cbz4BzCN, a long triplet lifetime universal host that can effectively harvest triplet excitons for phosphorescence and thermally activated delayed fluorescence OLED emission. Abstract : 35Cbz4BzCN, a novel universal host with a long triplet lifetime, has been developed. The triplet excitons in 35Cbz4BzCN can be effectively harvested by phosphorescence and thermally activated delayed fluorescence emitters. In the 4CzIPN doped device, the best performance of a maximum current efficiency of 111.8 cd A −1, power efficiency of 86.8 lm W −1, and external quantum efficiency of 31.7% with a small efficiency roll-off of 103 cd A −1 at 1000 cd m −2 has been achieved. 35Cbz4BzCN is also compatible with FIrpic to give sky-blue emission up to 46.3 cd A −1 and with TXO-TPA to give orange-red emission up to 60.6 cd A −1 efficiency.